Oil Price Shocks, Protest and the Shadow Economyː Is there a Mitigation Effect? - Phoebe W. Ishak; Ulrich Fritsche (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2020)
In this paper, we study the impact of exogenous variations of international oil prices on the incidence of protest, while exploring the role of the shadow economy as a mitigating factor. We find that oil price shocks are negatively associated with protests, but the effect is less severe the higher the initial size of the shadow economy. To explain these results, we show that the size of the shadow economy responds counter-cyclically to oil-price-driven income shocks. In particular, we find that the decline in the GDP per capita growth following a negative oil price shock leads to an increase in the size of the shadow economy. This suggest that the shadow economy's capacity to absorb persistent oil price fluctuations without provoking political unrest, should regard it as a mitigation tool rather than an economic burden.
Keywords: D74; O13; O17; Q34; 330; Oil Price Shocks; Protest; Shadow Economy; Income